The Effect of E-Filing System Implementation, Understanding of Taxation, and Facilitating Conditions on Taxpayer Compliance - Chelsea Anggriawan; Grace T. Pontoh; Syarifuddin Rasyid (International Journal of Educational and Life Sciences, 2024)
The study's findings demonstrate that the implementation of the e-Filing system has a favorable and substantial impact on taxpayer compliance. This suggests that better e-Filing system installation will result in higher taxpayer compliance. Tax knowledge has a favorable and considerable impact on taxpayer compliance. This implies that a taxpayer with a better understanding of taxes will be more compliant because they will know what happens to them if they don't file their taxes on time. Facilitating circumstances also have a good and substantial impact on taxpayer compliance. This suggests that when the tax office provides higher-quality services, taxpayer compliance will rise.